The problem of the ethical root of truth (A tribute to Antonio Rodríguez Huéscar on his birth centenary) - Padilla, Juan (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
This paper deals with the meaning of truth as «coincidence of man with himself» accordingto Ortega y Gasset and his disciple rodríguez huéscar. What the concept does not mean and which implications it has are also explained.